2013
DOI: 10.1093/abbs/gmt105
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde induces toxic effects and regulates the expression of damage response genes in BM-MSCs

Abstract: In this study, we assessed the toxic effects of formaldehyde (FA) on mouse bone marrow mesenchymal stem cells (BMMSCs). Cytotoxicity was measured by using MTT assay. DNA strand breakage was detected by standard alkaline comet assay and comet assay modified with proteinase K (PK). DNA -protein crosslinks (DPCs) were detected by KCl-SDS precipitation assay. We found that FA at a concentration from 75 to 200 mM inhibited cell survival and induced DPCs over 125 mM. The PK-modified comet assay showed that FA-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
1
4
0
1
Order By: Relevance
“…Our study shows that the mRNA and protein expression levels of XPC and ERCC1 in FA-treated BMSCs were significantly higher than those in the control cells, indicating that XPC and ERCC1 may be involved in the repair of human BMSCs DNA damage caused by FA. This is accordance with previous studies [7,39]. The mRNA and protein expression levels of XPA, XPC, and ERCC1 in cells incubated with FA plus APS groups at different concentrations were significantly higher than those in the FA-treated cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study shows that the mRNA and protein expression levels of XPC and ERCC1 in FA-treated BMSCs were significantly higher than those in the control cells, indicating that XPC and ERCC1 may be involved in the repair of human BMSCs DNA damage caused by FA. This is accordance with previous studies [7,39]. The mRNA and protein expression levels of XPA, XPC, and ERCC1 in cells incubated with FA plus APS groups at different concentrations were significantly higher than those in the FA-treated cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies have confirmed that formaldehyde (FA) could inhibit the proliferative activity and enhance DNA-protein crosslinks (DPCs) formation in mice bone marrow mesenchymal stem cells (BMSCs) [7]. Therefore, the main purpose of this study was to investigate the protective effect of Astragalus polysaccharide (APS) against cytotoxicity and genotoxicity in human BMSCs exposed to FA and its potential mechanisms.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, embryonic or normal tissue-derived stem cells and the patient’s own adult stem cells can be obtained and differentiated into various target tissues, including cardiomyocytes, hepatocytes, or neurons, for in vitro potential toxicity screening 21 . Especially, MSCs have been used for assessing the toxicity of various chemicals such as anesthetics 22 , 23 , chemotherapeutic drugs 24 , 25 , endocrine disruptors 26 , nanoparticles 27 , 28 , and other industrial chemicals including cosmetic ingredients or detergent 29 , 30 . Nevertheless, the comparison among the toxicological studies using MSCs is challenging, since laboratories around the world lack internationally standardized methods for isolation and in vitro expansion of MSCs, resulting in significant functional heterogeneity and inconsistent testing results.…”
Section: Discussionmentioning
confidence: 99%
“…73,74 Fare mezenkimal kök hücrelerinde formaldehitin çeşitli dozlarda uygulamasının yapıldığı in vitro bir çalışmada, 125 m ve üzeri dozlarda DNAprotein çapraz bağlanmaları, zincir kırıkları ve DNA hasar yanıtında rol alan Brca2, Rad51, Xrcc2, Xpa, Xpc, Chek1 ve Hus1 düzeylerinde artma gö-rülmüştür. 75 Tümör oluşumunun kök hücrelerdeki spontan mutasyonlardan kaynaklandığı hipotezinin araştırıldığı bir çalışmada fare kemik iliği mezenkimal kök hücreleri, in vitro kültür ile çok sayıda pasajı yapılarak, malign hücrelere dönüşüm aşamasında farelere enjekte edilmiş ve fibrosarkom oluşumu gözlenmiştir. Mezenkimal hücrelerin malign hücrelere dönüşümünün kromozom anormallikleri, artan telomeraz aktivitesi ve c-myc ekpresyonuna bağlı olarak gerçekleştiği sonucuna varılmıştır.…”
Section: Mezenki̇mal Kök Hücrelerdeki̇ Genotoksi̇si̇te çAlişmalariunclassified